Convection‐Permitting Hindcasting of Diurnal Variation of Mei‐yu Rainfall Over East China With a Global Variable‐Resolution Model. Issue 14 (20th July 2021) - Xu, Mingyue; Zhao, Chun; Gu, Jun; Feng, Jiawang; Hagos, Samson; Leung, L. Ruby; Luo, Yali; Guo, Jianping; Li, Rui; Fu, Yunfei
Abstract: Two sets of 48‐h hindcast experiments for Mei‐yu season using non‐hydrostatic global variable‐resolution model (MPAS‐Atmosphere) with regional refinement at 4 km resolution (V4km) and uniform 60 km resolution (U60km) are first‐time conducted to attempt at simulating the Mei‐yu rainfall in 2015 over East China. The analysis focuses on the seasonal average of diurnal variation of precipitation amount (PA), intensity (PI), and frequency (PF). Both simulations reasonably reproduce the spatial distribution of PA. V4km is more skillful in simulating the spatial distributions and magnitudes of PF and PI. The diurnal cycle of Mei‐yu rainfall shows a major early morning peak and a minor afternoon peak, contributed by precipitation during two sub‐periods with distinct synoptic circulations. With strong Mei‐yu in the first sub‐period, the diurnal variation of PA is controlled by nocturnal southwesterly jet. V4km overestimates the morning peak mainly due to its bias in simulating boundary layer inertial oscillation. Although differences in PA between the simulations are small, U60km overestimates PF and underestimates PI. With weak Mei‐yu in the second sub‐period, the diurnal variation of PA is controlled by both synoptic circulation and local convection. At both resolutions, deviations in the large‐scale circulation modulated by a few typhoons lead to positive biases in the morning peak of PA. After removing the typhoon impacts, V4km captures the observed diurnal cycle of PA well, while U60km significantly underestimates PA and PI particularly in the afternoon. Future studies focusing on advancing modeling of southwesterly jet and typhoons may further improve convection permitting simulation of Mei‐yu rainfall. Key Points: Global modeling at V4km is more skillful in reproducing Mei‐yu rainfall characteristics compared to modeling at U60km With strong Mei‐yu, differences in rainfall diurnal variation controlled by nocturnal southwesterly jet are small between U60km and V4km With weak Mei‐yu, V4km produces better rainfall diurnal variation controlled by multi‐scale processes compared to U60km